Nanoparticles Based Extraction Strategies for Accurate and Sensitive Determination of Different Pesticides - Erarpat, Sezin; Bodur, Suleyman; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2022)
Sample preparation methods have become indispensable steps in analytical measurements not only to lower the detection limit but also to eliminate the matrix effect although more sophisticated instruments are being commonly used in routine analyses. Solid phase extraction (SPE) is one of the main extraction/preconcentration methods used to extract and purify target analytes along with simple and rapid procedures but some limitations have led to seek for an easy, sensitive and fast extraction methods with analyte-selective sorbents. Nanoparticles with different modifications have been used as spotlight to enhance extraction efficiency of target pesticides from complicated matrices. Carbon-based, metal and metal oxides, silica and polymer-based nanoparticles have been explored as promising sorbents for pesticide extraction. In this review, different types of nanoparticles used in the preconcentration of pesticides in various samples are outlined and examined. Latest studies in the literature are discussed in terms of their instrumental detection, sample matrix and limit of detection values. Novel strategies and future directions of nanoparticles used in the extraction and preconcentration of pesticides are also discussed.
Keywords: Nanoparticles; pesticides; solid phase extraction (SPE); magnetic solid phase extraction (MSPE); dispersive solid phase extraction (DSPE); Chemistry